Cross-species transmission of poultry pathogens in backyard farms: ducks as carriers of chicken viruses - Maude Pauly (2020)
© 2019, © 2019 Houghton Trust Ltd. In backyard farms of Lao People’s Democratic Republic, mixed-species rearing of poultry is a breeding-ground for cross-species transmission. Here, the epidemiology of viruses circulating among backyard poultry in Vientiane Province was assessed to guide future control strategies. Oral/tracheal and cloacal swabs, collected from 605 poultry (308 ducks, 297 chickens) between 2011 and 2015, were screened by PCR for Newcastle disease virus (NDV), coronavirus (CoV) and chicken anaemia virus (CAV). Chicken sera were screened for anti-NDV antibodies by ELISA. Statistical and phylogenetic analyses revealed transmission patterns and relationships. Closely related strains co-circulated in chickens and ducks. While CoV RNA was detected in oral/tracheal swabs of 9.3% of the chickens and 2.4% of the ducks, rates were higher in faecal swabs of both species (27.3% and 48.2%). RNA of infectious bronchitis virus (IBV) and duck CoV was found in faecal swabs of chickens (19.7% and 7.1%) and ducks (4.1% and 44.1%). Moreover, DNA of the generally chicken-specific CAV was detected in oral/tracheal swabs of chickens (18.1%) and, sporadically, of ducks (2.4%). Despite serological evidence of NDV circulation or vaccination (86.9%), NDV RNA was not detected. We found a high prevalence and indication for cross-species transmission of different CoV strains in backyard poultry. Interestingly, ducks served as biological, or at least mechanical, carriers of viral strains closely related not only to IBV, but also to CAV. Bird containment and poultry species separation could be first steps to avoid cross-species transmission and emergence of novel strains with broad host range and enhanced pathogenicity. RESEARCH HIGHLIGHTS High rates of avian viruses were detected by PCR in backyard poultry from Lao PDR. Diverse coronavirus and chicken anemia virus strains co-circulated. Phylogenetic analyses suggested virus transmission between chickens and ducks. Serological evidence of Newcastle disease was found, but viral RNA was not detected.